Information and Communication Technologies in Tourism 2016 2016
DOI: 10.1007/978-3-319-28231-2_56
|View full text |Cite
|
Sign up to set email alerts
|

Value Co-creation and Co-destruction in Connected Tourist Experiences

Abstract: Information and communication technologies (ICTs) have become a key resource that has transformed travel and tourist experiences. Due to the increasing ubiquity and mobility of ICTs, they have become integral in creating connected experiences that interlink travel with everyday life. While recent studies have investigated value co-creation and the enhancement of experiences through ICTs, there is less knowledge about potential value co-destruction when ICTs come into place. This paper provides a first explorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 34 publications
3
87
0
2
Order By: Relevance
“…It is arguably no longer normal to be disconnected and Wang et al (2014) found that tourists were influenced by subjective norms, specifically peer mobile use patterns, and that routines of smartphone use from everyday life pervaded the tourist experience. However, there are questions about whether this is desirable (Brooks & Longstreet, 2015;Llamas & Belk, 2013;Neuhofer, 2016), for example, Paris et al (2015) found remaining connected to work while a tourist can be a blessing, but also cause anxiety and sociologists have explored in general whether technology weakens, reinforces or supplements co-present sociability (Fortunati, Taipale, & de Luca, 2013).…”
Section: Digital (Dis)connection In Tourismmentioning
confidence: 99%
See 3 more Smart Citations
“…It is arguably no longer normal to be disconnected and Wang et al (2014) found that tourists were influenced by subjective norms, specifically peer mobile use patterns, and that routines of smartphone use from everyday life pervaded the tourist experience. However, there are questions about whether this is desirable (Brooks & Longstreet, 2015;Llamas & Belk, 2013;Neuhofer, 2016), for example, Paris et al (2015) found remaining connected to work while a tourist can be a blessing, but also cause anxiety and sociologists have explored in general whether technology weakens, reinforces or supplements co-present sociability (Fortunati, Taipale, & de Luca, 2013).…”
Section: Digital (Dis)connection In Tourismmentioning
confidence: 99%
“…The separation requires both physical travel and also a state of mind which depends on how much cultural baggage comes with the tourist (Jafari, 1987). This is captured by the escape motive in tourism literature (Dann, 1981;Hall, 2003;Krippendorf, 1987) however, mobile connectivity alters the idea of escape (Neuhofer, 2016). Though tourists who travel to other places clearly physically escape their home and work surroundings, they can now easily remain connected and interact with the home environment.…”
Section: Digital (Dis)connection In Tourismmentioning
confidence: 99%
See 2 more Smart Citations
“…augmented reality) įtaka vartotojams (Chung ir kt., 2015) renkantis keliones. Be to, vis labiau orientuojamasi į visapusišką ir subjektyvų / asmeninį / autentišką šiuolaikinio išmanaus keliautojo patyrimą (Neuhofer, 2014;2016), analizuojamos sumaniojo turizmo ekosistemos (Gretzel ir kt., 2015;Boes, 2016) ir jų perteikimas turizmo organizatorių veikloje.…”
Section: Socialinių Medijų Formų įTaigos Renkantis Vietos Turizmo Orgunclassified